WHEN IS TRANSLATION LEGAL? - GAŁUSKINA, Ksenia (Comparative Legilinguistics, 2011)
The author focuses her attention on the term legal translation. The aim of the paper is to give features of legal translation which can serve the purpose of constructing a definition of the term. The first part of the paper touches upon the problem of legal translation, legal discourse, legal texts and legal language. The typologies of legal texts presented by different authors have been included here as well. In the second part of the article the features typical of legal translation and differentiating it from other types of translation are given.